DEVELOPMENT OF NUCLEAR MEDICINE IN UZBEKISTAN AND ASSESSMENT OF RADIATION RISKS - Zaredinov D.A.; Li M.V.; Goziyev S.O. (Central Asian Journal of Medicine, 2025)
The development of nuclear medicine in the Republic of Uzbekistan is interconnected with the introduction of new technologies and necessitates the development and updating of methods for optimizing diagnostic radionuclide studies. The article presents the results of a study of the current state of nuclear medicine in the republic, the dynamics of the development of new technologies and methods in nuclear medicine for 2022-2025. Radiopharmaceuticals produced by the Institute of Nuclear Physics at the Academy of Sciences of the Republic of Uzbekistan and used in radioisotope departments of medical institutions were studied. Hybrid studies of positron emission tomography and computed tomography patients in medical centers in Tashkent were studied. During the research work, the effective radiation doses of patients were calculated, followed by an assessment of the risks of stochastic effects.